Analysis of Factors Influencing The Implementation of Sustainable Construction Management Towards Project Waste Management in The National Capital City - Ardiasa Septasawala; Endah Kurniyaningrum; M. Zaki M. Zaki; Inavonna Inavonna (Green Publisher Indonesia, 2025)
The construction industry currently contributes 13% to the world's Gross Domestic Product (GDP), uses 36% of global energy and produces 39% of energy-related CO2 emissions. The application of Environment, Social, and Governance (ESG) principles is increasing in construction management to achieve sustainability. The construction sector brings diverse impacts on the environment, especially through significant construction waste. The relocation of the National Capital City (IKN) to East Kalimantan has the principles of smart city, forest city, and sponge city which carry the concept of sustainable construction. So this study will analyze the factors that influence the implementation of sustainable construction management on project waste management in IKN. The method used is a survey method with a quantitative method approach and the research variables used are based on the results of a literature review. So that from the results of the analysis it is concluded that the factors that influence sustainable construction management on waste management are Energy Efficiency, where the indicator that has the highest value is the use of energy-efficient plants, machinery and equipment. This is because the implementation of work at IKN cannot be separated from a development approach that prioritizes the use of wise, efficient resources and minimal environmental impact.